Policies and issues on Philippine fisheries and aquatic resources. - Garcia, M. Jr. P. (Los Banos, Laguna PCAMRD, 1992)
PCAMRD Book Series no.14/1992
Keywords: Use; Fisheries; Fisheries code; Policies; Philippine--Fishery laws